Professional Master's Program in Biotechnology and Innovation Management: The Triple Helix in movement and knowledge generation. Issue 4 (August 2022) - Baeta, Adelaide Maria Coelho; Liboreiro, Karla Rocha; Diniz, Marcia Consuelo; Padrão, Vanessa Paiva; Teixeira, Camila Palhares
This paper analyses evidence of innovation in the joint work of a company, a university and government in creating a professional Master's degree program in Biotechnology and Innovation Management at the Centro Universitário de Sete Lagoas, Minas Gerais, Brazil. It presents a new perspective by combining two fields of knowledge: biotechnology and innovation management. The conceptual scheme of Triple Helix spaces is still not well analyzed from an empirical viewpoint. This paper identifies the development of knowledge, consensus and innovation spaces through an examination of this professional Master's course. A qualitative approach was used for the conducting of 20 semi-structured interviews with representatives of the Triple Helix: two directors of Embrapa, a Brazilian agriculture and livestock research company; the President of FAPEMIG, the Minas Gerais Research Support Foundation; nine teachers; and eight students. In addition, data were analyzed from the databases of CAPES (Coordination for the Improvement of Higher Education Personnel). The results show that the proximity between the knowledge areas of biotechnology and innovation management strengthened this new program, created only 7 years ago, which has already impacted socio-economic regional development.